Using Linked Administrative Data to Measure Earnings Mobility of Public Assistance Recipients during the Great Recession - Sally Wallace; David Sjoquist; Brett Mullins (International Journal of Population Data Science, 2019)
There is a great deal of interest and concern in the trends in income inequality in the United States and how it inequality has changed since the Great Recession. Various reasons for this divide have been offered but are notoriously difficult to evaluate due to data constraints. Public sector programs aimed at alleviating poverty are also difficult to measure because of data issues. In this paper, we estimate the impact of one of the largest federal support programs in the U.S. on income mobility of at risk populations. The Supplemental Nutrition Assistance Program (SNAP) serves low income families by providing significant food benefits.